Exploring China’s farmer-level water saving mechanisms: Analysis of an experiment conducted in Taocheng district, Hebei Province - Chen, S.; Wang, Y.; Zhu, T. (MDPI, 2014)
Two types of farmer-level mechanisms have been traditionally adopted to increase agricultural water use efficiency in northern China: pricing mechanisms and tradable water rights systems. However, the reluctance of policymakers to exacerbate farmers’ burdens has rendered pricing mechanisms politically infeasible, while tradable water rights systems involve prohibitively high transaction costs in rural China. An experiment conducted in 2005 in the Taocheng District of Hebei Province created a new kind of water-saving mechanism that involves a number of institutional innovations, including “flexible total management”, “collect then refund” and “collect and subsidize, then refund”. This paper evaluates the district’s water-saving mechanisms based on efficiency, equity and operability criteria. The results of the analysis demonstrate that the “collect then refund” mechanism can more effectively enhance water use efficiency and reduce farmers’ burdens than water pricing instruments, tradable water rights systems and flexible total management. Adequate infrastructure and trusted institutions are identified as necessary prerequisites for the successful implementation of the new water-saving mechanism. We believe the new mechanism has great potential to be scaled up.